AN INVESTIGATION OF INTERLINGUAL AND INTRALINGUAL INTERFERENCE FOUND IN ENGLISH AS A FOREIGN LANGUAGE (EFL) STUDENTS’ COMPOSITION OF RECOUNT TEXT - Nur Raissah; Zulfadli A. Aziz (Universitas Syiah Kuala, 2020)
Due to the complexity of writing skill, EFL students, especially in Aceh, face a lot of problems in composing a text such as a recount text resulting in abundant errors of both interlingual and intralingual interferences. Considering this, this study aims at identifying the types of interlingual and intralingual errors committed by the students in writing recount text. Based on the results found in the written samples collected from 60 students, it was found that from 16 sorts of error categories, the students committed 1143 occurrences of errors. The types of interlingual errors collected were in reference to orthographic errors, lexical errors, and grammatical errors, while the type of intralingual errors was overgeneralization, ignorance of rule restriction, incomplete application of rules, and false concepts hypothesis. All of these were caused by the lack of vocabulary and having no idea of the right words for their ideas, and hence, they just directly translated their story literally from bahasa to English. Therefore, both teachers and students should be aware of this condition. Moreover, the creativity of the teachers in enhancing students’ vocabulary and using it in context is truly required. Hence, these problems can be resolved in the best way.